إشتقاق سبين الإلكترون والحركة الارتجاجية في معادلة ديراك (مجلة جامعة اللاذقية - سلسلة العلوم الأساسية, 2018)
The integration between the special relativity theory and quantum mechanics through the Dirac equation yielded many paradoxes that remained unsolved until the last years, like the Zitterbewegung problem. Besides, the spin prediction from the Dirac equation could be identified only with non-relativistic approximations (Pauli and Foldy-Wouthysen). In this paper, we showed that the derivation of the spin and its magnetic moment can be done through a classical treatment without approximation. By this approach a modified Dirac equation was obtained, which also eliminates the problem of the Zitterbewegung. أدى الجمع بين نظرية النسبية الخاصة و ميكانيك الكم من خلال معادلة ديراك (Dirac) إلى نشوء عدة مسائل، والتي بقيت دون حل حتى السنوات الأخيرة. و منها مشكلة الحركة الارتجاجية (Zitterbewegung)، بالإضافة إلى أن إظهار سبين الإلكترون و عزمه المغاطيسي من معادلة  Diracيمكن أن يتم فقط بشكل غير مباشر و ذلك باستخدام عمليات تقريب لانسبوية كتقريبي Pauli و Foldy-Wouthysen. في هذا البحث نبين أنه يمكن استنتاج سبين الإلكترون و عزمه المغناطيسي من خلال معالجة تقليدية دون استخدام عمليات تقريب، و ذلك بتعديل معادلة ديراك (Dirac equation)، و الذي يؤدي أيضا لحل مشكلة الحركة الارتجاجية.